1999
DOI: 10.1037/0022-3514.76.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry and perceived facial attractiveness: A monozygotic co-twin comparison.

Abstract: Symmetry is a major correlate of physical attractiveness across species, including humans. Investigating the nature of this relationship has been difficult, however, for several reasons, including the facts that variance in symmetry is attributable to more than one source and is often correlated with other variables related to attractiveness. This study assessed the role of facial symmetry in relation to perceptions of facial attractiveness. Some of the natural covariates of symmetry were controlled for by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
11

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(117 citation statements)
references
References 62 publications
2
104
0
11
Order By: Relevance
“…In addition, they replicate earlier positive correlations between symmetry and attractiveness (Grammer & Thornhill, 1994;Jones & Hill, 1993;Zebrowitz et aI., 1996). They are also consistent with a recent report that symmetry differences between identical twins correlate positively with differences in attractiveness (Mealey & Townsend, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, they replicate earlier positive correlations between symmetry and attractiveness (Grammer & Thornhill, 1994;Jones & Hill, 1993;Zebrowitz et aI., 1996). They are also consistent with a recent report that symmetry differences between identical twins correlate positively with differences in attractiveness (Mealey & Townsend, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…Studies of naturally occurring human facial asymmetries provide evidence that symmetrical faces are attractive, showing that measured symmetry is positively correlated with attractiveness judgements (facialmetric measures (Grammer & Thornhill 1994;Scheib et al 1999;Jones et al 2001) and psychophysical measures (Mealey et al 1999;Penton-Voak et al 2001)). Consistent with preferences for naturally occurring symmetry in real faces, four recent computer graphic studies (Rhodes et al 1998(Rhodes et al , 2001bPerrett et al 1999;Little et al 2001; but see Swaddle & Cuthill 1995) have shown preferences for faces manipulated to increase symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…3 Clinically, left-right symmetry of the underlying skeletodental structures generally is a treatment goal, 4,5 and studies suggest that symmetric faces are deemed more attractive. 6,7 Some asymmetries are acquired, for example, because of chewing side preference 8 or trauma, 9,10 but most left-right differences have no specific, identifiable etiology. 11,12 Most asymmetries are subtle, requiring precise bilateral comparisons for their detection.…”
Section: Introductionmentioning
confidence: 99%